Kolaborasi Karya Tari Suara Hati - Supendi, Eko; Sri Kuncoro, Jonet; Suroto, Suroto (Institut Seni Indoensia Surakarta, 2023)
Research on art creation entitled Suara Hati Dance Collaboration involving dancers (students) and children with visual impairments (disabilities) to answer concerns about how a dancer feels dancing in the dark. This research method is a collaboration between the potential of dancers and the artistic potential of blind children. The dancers’ explorations were inspired by the behavior of the character Gendari in the Mahabarata story, who closed his eyes all his life only to feel the same darkness as his husband, Destrarastra. Exploring the potential of blind children is an important part of this research to determine the process and form of work. The results of this study provide an artistic experience for dancers, moving in the dark just following their auditory instincts. Providing space for expression and artistic experience for blind children, fostering self-confidence, courage, and a sense of pride in being able to work with dancers and appear in performances that are shown publicly.Keywords: voice, heart, collaboration, visual impairment, Gendari, movement, darkness.